Gestión Financiera en las Cooperativas de Ahorro y Crédito del Segmento 2 en la provincia de Chimborazo, periodo 2022-2023 - Morocho Muyolema, Lizbeth Katherine (2026)
The objective of this research is to analyze “Financial management in savings and credit cooperatives in segment 2 of the province of Chimborazo during the period 2022-2023”. The study applied a qualitative approach using an inductive method, which enabled the examination of specific cases through the analysis of financial statements and the implementation of questionnaires directed at managers, financial officers, and accountants of the following cooperatives: 4 de Octubre, Educadores de Chimborazo, Lucha Campesina, Minga Ltda., and Visión de los Andes. The research was descriptive and documentary, employing a non-experimental design since the financial reality was observed without manipulation. The findings reveal significant variations in financial management among the cooperatives. Some, such as COAC 4 de Octubre, demonstrate solid financial structures, sustained growth, and favorable profitability, whereas others, such as Visión de los Andes, exhibit weaknesses related to high dependence on external financing and low profitability. The financial assessment showed that, overall, cooperatives increased their assets and equity; however, not all succeeded in converting this growth into efficient profitability. Additionally, it was identified that not all institutions consistently apply financial analysis tools or maintain adequate internal controls, limiting timely decision-making. The study concludes that strengthening financial management through training, the use of financial indicators, and strategic planning is essential to ensure the stability and sustainability of Segment 2 cooperatives.